SISTEM PENDUKUNG KEPUTUSAN REKOMENDASI PEMILIHAN SMARTPHONE TERBAIK MENGGUNAKAN METODE TOPSIS - Anggi Eryzha; Solikhun Solikhun; Eka Irawan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Smartphones are a primary need for all upper class and lower class people. As these needs are many smartphone vendors that offer different prices, features, systems and technologies at competitive prices. Many people want specifications that are capable but limited in financial terms. This causes smartphone users not to be able to make the right choice according to their needs because the frequent selection of smartphones is based on prestige and consumer consumptive behavior. The TOPSIS method is a multicriteria method used to identify solutions from alternative sets based on simultaneous minimization of the ideal point distance and maximizing the distance from the lowest point. The expected results can be input to potential smartphone buyers in accordance with their finances and qualified specifications.Keywords: Decision Support System, Topsis Method, Smartphone.